Lá onde há poder, há resistência : a resistência no pensamento de Michel Foucault no período de 1975-1976 - Branco, Rosele Maria (2013)
The objective of this dissertation is to comprehend the meaning of the resistance through a reading of Surveiller et punir and La volonté de savoir: Histoire de la sexualité 1, by Michel Foucault. Based on the historic studies about the powers and the knowledges, submitted in those two books and in other texts by the author, during the period of 1975-1976, considered the questions how is it possible to resist? which perspectives of resistance Foucault proposed? This started from the dynamic aspect of the conception of power sustained by him, understood as relations of forces, and the critical stance they take their genealogical analysis, to try to build models of resistance. It defends the rapprochement between the two books, through the link of modalities of power they exhibit the disciplinary power and the biopolitics. The term resistance means pointing out the openings in the power relations that could carry out the transformative struggles. This work contributed to the reconstruction of various forms of resistant attitudes, perceived at two levels. A most exemplary level of perception, in Surveiller et punir, gathers forms of possible reactions to the attributes of disciplinary power. In another more general, in La volonté de savoir, the types of resistance are constituted as key to intelligibility situations in opposition to power, as an instrument for interpreting the strategic positioning of the discourses and also as inspiration for renovating attitudes. The elements of the art of living, inserted in the reflections on biopolitics, refer to later developments in the thought of Michel Foucault, concerning the theme of the resistances